The Mechanism of Assessing Human’s Economic Excellence by Using “KPI” Tools (Global Journal of Management and Business Research, 2023)
The article describes the concept of human economic excellence An algorithm for the calculation of the multiplier of human economic excelence is recommended in five stages Significant skill indicators for evaluating a person s economic excellence by using the KPI tool has been produced On the basis of these assessment indicators four quality levels were determined a person with economic excellence a person with economic maturity a person with economic potential and a person without economic excellence based on the author s method of evaluating the real economic excellence of 500 employed people in the Bukhara region of the Republic of Uzbekistan
Keywords: economically perfect person; work ability; entrepreneurial ability; economic excellence; economically skilled person